2020
DOI: 10.3390/nu12010259
|View full text |Cite
|
Sign up to set email alerts
|

Potential Role of Tocotrienols on Non-Communicable Diseases: A Review of Current Evidence

Abstract: Tocotrienol (T3) is a subfamily of vitamin E known for its wide array of medicinal properties. This review aimed to summarize the health benefits of T3, particularly in prevention or treatment of non-communicable diseases (NCDs), including cardiovascular, musculoskeletal, metabolic, gastric, and skin disorders, as well as cancers. Studies showed that T3 could prevent various NCDs, by suppressing 3-hydroxy-3-methylglutaryl-coenzyme A reductase (HMGCR) in the mevalonate pathway, inflammatory response, oxidative … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
34
0
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 60 publications
(50 citation statements)
references
References 388 publications
(711 reference statements)
2
34
0
4
Order By: Relevance
“…The tocotrienol-rich-fraction (TRF) of palm oil has been anticipated as an e cient alternative for αtocopherol due to its potent antioxidant properties in vitro (41)(42)(43)(44)(45). Although there was no report on TRF effect on HSP70, the present study ndings are in agreement with a number of studies that suggest a higher antioxidant potency of tocotrienols compared to tocopherols in vitro; as HSP70 reduction has been earlier related in this discussion to vitamin E antioxidant function.…”
Section: Comparative Effect Of α-Tocopherol and Palm-tocotrienol Richsupporting
confidence: 90%
“…The tocotrienol-rich-fraction (TRF) of palm oil has been anticipated as an e cient alternative for αtocopherol due to its potent antioxidant properties in vitro (41)(42)(43)(44)(45). Although there was no report on TRF effect on HSP70, the present study ndings are in agreement with a number of studies that suggest a higher antioxidant potency of tocotrienols compared to tocopherols in vitro; as HSP70 reduction has been earlier related in this discussion to vitamin E antioxidant function.…”
Section: Comparative Effect Of α-Tocopherol and Palm-tocotrienol Richsupporting
confidence: 90%
“…Tocols can limit lipid peroxidation in cell membranes and scavenging reactive oxygen species and protect tissues from consequent oxidative damage. Thus, supra-nutritional doses of tocols have been reported for cardiovascular diseases, cancer, chronic inflammation, Alzheimer's disease, and Parkinson's disease [9]. Tocotrienols are reported to be superior to tocopherols in the prevention and treatment of major chronic diseases, as their unsaturated chain facilitating cell penetration is highly antioxidative [10].…”
Section: Introductionmentioning
confidence: 99%
“…33 These special properties of tocotrienols have been reported in various in vitro studies using different cell lines (breast, lung, liver, pancreas, skin, and bladder cancers). 34,35 Several in vivo studies have also shown that tocotrienols successfully accumulate in cancer cells but not in normal tissues. 36,37 Previous studies demonstrated that δ-tocotrienol (200 mg/kg) significantly enhanced the efficacy of gemcitabine to inhibit pancreatic cancer growth and survival in vitro and in vivo by suppressing NF-kB activity.…”
mentioning
confidence: 99%